FORMULASI DAN EVALUASI IN VITRO MIKROEMULSI A/M KOMBINASI KAFEIN DAN EKSTRAK ETANOL PEGAGAN (CENTELLA ASIATICA) SEBAGAI ANTISELULIT - Destira, Maya
Cellulite is a skin surface bumpy, rough and uneven that resembles orange peel skin commonly found in adult women. Cellulite was caused by alteration of interstitial matrix and cause accumulation of adiposite and disorder of microcirculation. Caffeine inhibit phospodiesterase enzyme which can increase the lipolysis process. Asiaticoside from pegagan (Centella asiatica) used to increase the microcirculation. Cellulite occur in hypodermis layer, a good drug delivery system was needed to deliver the active ingredients until hypodermis layer. The purpose of this study was to formulate microemulsion W/O using combination of caffeine and ethanol extracts of pegagan as anticellulite. Formulation of microemulsion used VCO as oil phase, water, ethanol and glycerin as cosurfactan, Croduret 50 SS as surfactan, prophyl paraben, and methyl paraben as preservatives. Optimization of microemulsion base formulation included optimization of ratio cosurfactant, cosurfactant-surfactant, and the amount of water phase. The result of this optimization was constructed into pseudoternary diagram. The optimum base formulation which formed a clear W/O miroemulsion was choosen to deliver caffeine and ethanol extract of pegagan. Evaluation of microemulsion include organoleptic evaluation, pH, viscosity, droplet size determination, physical stability test using centrifugation and free-thaw methods, determination of caffeine concentration in microemulsion, and determination of asiaticoside content in the extract and microemulsion. In vitro test skin permeation of microemulsion was determined using Franz cell difusion with snake skin membran. Microemulsion showed a cleargreen appereance with viscosity of 1729.28 ± 46.09 cPs, pH of 5.72 ± 0.06. There was not statisticaly significant different in organoleptic, viscosity for 28 days storage at room temperatur, and pH was in the range 5.5 – 6.2. Based on a 3750 rpm centrifugation for 5 hours, there was no phase separation. In the freeze-thaw test there was an increasing droplet size that was not statisticaly significant different and still gave a clear microemulsion appereance. The average droplet diameter was 19.11 nm. Caffeine content in the microemulsion was 0.478 ± 4,5.10 -3 %. Concentration of asiaticoside in the extract was 5.79 ± 0,059% and concentration asiaticoside in microemulsion was 0.11 ± 1.12.10 -3 %. The results of in vitro test were cumulative amount of caffeine that can be penetrated for 8 hours were 293.89 ± 118.89 µg.cm -2 or 67.27 ± 27.21%. A stable microemulsion W/O combinations of caffeine and ethanol extracts pegagan consist of aquades 10%, Croduret 50 SS 35%, ethanol 7%, glycerin 28%, caffeine 0.5%, etanol extract pegagan 2%, methylparaben 0,2%, prophylparaben 0.022%, ad VCO up to 100%, and expected to have potential to use as anticellulite.